A Systematic Literature Review of Determinant Factors of BIPA Learning Success - Faizin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Bahasa Indonesia bagi Penutur Asing (BIPA) learning holds an essential role in promoting Indonesian culture and language to the international community. Hence, the successful learning of BIPA needs to be continuously improved to support the achievement of the mission. One way to enhance successful BIPA learning is to know the factors that influence the learning process. However, research on BIPA learning determinants remains fragmented and lacks comprehensive synthesis. This article aims to identify the determinants of the success of BIPA learning based on a Systematic Literature Review with the PRISMA method. A systematic search was conducted using google scholar and google search for studies published between 2015-2024. Following identification, screening, eligibillity, and inclusion processes, a total 11 studies were included studies in the final review. Based on the systematic analysis of the 11 included studies, it was found that factors such as teacher quality, culture-based learning models, use of technology, program management, and learner motivation are the main factors that influence the success of BIPA learning. The success of BIPA learning is greatly influenced by the integration of these factors, which support each other. These findings imply thaat BIPA teachers and program managers should consider these factors in an integrated manner when ddesssigning and implementing BIP learning programs. Based on these findings, it is suggested that future research should focus on analyzing the relationship between these factors and their influence on creating effective learning experiences.